Unraveling teacher stressors in Bhutan: a qualitative exploration of contributing elements - Dorji, Tenzin (Frontiers in Education, 2024)
School teaching is widely acknowledged to be a highly demanding profession.Consequentially, an emerging academic literature deals with the stress levels teachers face. While existing studies predominantly focus on quantifying relevant stressors, this study investigates the subjective perceptions and interpretations of stressors by teachers.Data comes from Bhutan, a country with a high teacher resignation rate primarily due to teacher stress, despite being one of the highest-paid occupations. The results show that teacher stress in Bhutan predominantly emanates from heightened job demands. These demands are perceived differently in terms of how individuals view teaching responsibilities and non-academic obligations [e.g., Class Teacher]. The pervasive impact of inadequate leadership and management exacerbates stress levels, directly encroaching upon psycho-social well-being. Ten teachers in Bhutan were interviewed using a semistructured format. The interview data was recorded, transcribed, and coded using MAXQDA. Thematic analysis was then conducted based on the generated codes. By adopting a qualitative lens, this research enriches our understanding of teacher stress by unravelling how stressors are interconnected and how different teachers perceive the same stressor differently, providing insights on targeted interventions and support Deleted: semi-structured interviews with teachers in Deleted: repatriation mechanisms. The results also show that supportive leadership can sometimes be viewed as a source of stress as opposed to the popular notion of perceiving it entirely as a stressmitigating factor.